2019
DOI: 10.1002/hipo.23154
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of the long axis of the hippocampus and ventromedial prefrontal cortex in schema‐related memory retrieval

Abstract: When new information is relevant to prior knowledge or schema, it can be learned and remembered better. Rodent studies have suggested that the hippocampus and ventromedial prefrontal cortex (vmPFC) are important for processing schema‐related information. However, there are inconsistent findings from human studies on the involvement of the hippocampus and its interaction with the vmPFC in schema‐related memory retrieval. To address these issues, we used a human analog of the rodent spatial schema task to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(62 citation statements)
references
References 68 publications
2
44
1
Order By: Relevance
“…Furthermore, while both posterior and anterior hippocampus exhibited significant story-specific representation at encoding, the correlation between encoding story scores and subsequent memory was significantly larger for posterior hippocampus. Taken together, these results suggest that posterior hippocampus plays an especially important role in representing story-specific details, consistent with theories of gist vs. detail representations in the hippocampus (Guo and Yang, 2020…”
Section: Relationship Between Schematic Representations During Encoding and Subsequent Memorysupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, while both posterior and anterior hippocampus exhibited significant story-specific representation at encoding, the correlation between encoding story scores and subsequent memory was significantly larger for posterior hippocampus. Taken together, these results suggest that posterior hippocampus plays an especially important role in representing story-specific details, consistent with theories of gist vs. detail representations in the hippocampus (Guo and Yang, 2020…”
Section: Relationship Between Schematic Representations During Encoding and Subsequent Memorysupporting
confidence: 86%
“…Given the strong involvement of mPFC during schematic encoding, it has been hypothesized that mPFC may play a role at retrieval by providing schematic cues for memory search (van Kesteren et al, 2012). While some studies have found that schema-related activity in mPFC during retrieval benefits memory (Brod et al, 2015;van Kesteren et al, 2010b;Müller et al, 2020;Webb and Dennis, 2019;Raykov et al, 2021), others have not (van Buuren et al, 2014;Webb et al, 2016;Guo and Yang, 2020;van der Linden et al, 2017;Reagh et al, 2021). In our study, we did not observe strong mPFC schema reinstatement, nor were able to relate it to a behavioral memory benefit.…”
Section: Relationship Between Schematic Representations During Retrieval and Memory Performancecontrasting
confidence: 69%
See 2 more Smart Citations
“…The prefrontal cortex (PFC) contributes to numerous advanced brain functions (D'Esposito et al, 2000;Davidson et al, 2006). Both the lateral and medial surfaces of the PFC receive projections from medial temporal lobe (MTL) and thalamus, which are part of the recognition memory network (Banks et al, 2012;Pergola and Suchan, 2013;Preston and Eichenbaum, 2013;Guo and Yang, 2019) which are critical for recall (Cohen et al, 2018). Medial prefrontal cortex (mPFC) plays a critical role in remote, recent and short-term memories over a broad range of tasks (Euston et al, 2012).…”
Section: Introductionmentioning
confidence: 99%